Vergara, Germán. Fueling Mexico. Energy and Environment, 1850- 1950. Cambridge: Cambridge University Press, 2021. 322 pp - Paolo Riguzzi (H-Industri@)
Reseña de Vergara, Germán. Fueling Mexico. Energy and Environment, 1850-1950. Cambridge: Cambridge University Press, 2021.